RUSSIAN MODERNISATION AND NEW GLOBAL DISPOSITION - Iosif Diskin (Сравнительная политика, 2015)
Abstract: The need to overcome dependence from energy commodities, as well as to create macro-social system enabling human potential of Russian citizens, defines the priorities of Russian modernisation. Russian economy should be focused on creation of innovative products and sectors with high added value. Today such activity demands cooperation with other major powers with due account of their changing role in the international system.